Discontinuing disease-modifying therapy in MS after a prolonged relapse-free period: a propensity score-matched study. Issue 10 (13th June 2016) - Kister, Ilya; Spelman, Tim; Alroughani, Raed; Lechner-Scott, Jeannette; Duquette, Pierre; Grand'Maison, Francois; Slee, Mark; Lugaresi, Alessandra; Barnett, Michael; Grammond, Pierre; Iuliano, Gerardo; Hupperts, Raymond; et al.
Abstract : Background: Discontinuation of injectable disease-modifying therapy (DMT) for multiple sclerosis (MS) after a long period of relapse freedom is frequently considered, but data on post-cessation disease course are lacking. Objectives: (1) To compare time to first relapse and disability progression among 'DMT stoppers' and propensity-score matched 'DMT stayers' in the MSBase Registry; (2) To identify predictors of time to first relapse and disability progression in DMT stoppers. Methods: Inclusion criteria for DMT stoppers were: age ≥18 years; no relapses for ≥5 years at DMT discontinuation; follow-up for ≥3 years after stopping DMT; not restarting DMT for ≥3 months after discontinuation. DMT stayers were required to have no relapses for ≥5 years at baseline, and were propensity-score matched to stoppers for age, sex, disability (Expanded Disability Status Score), disease duration and time on treatment. Relapse and disability progression events in matched stoppers and stayers were compared using a marginal Cox model. Predictors of first relapse and disability progression among DMT stoppers were investigated using a Cox proportional hazards model. Results: Time to first relapse among 485 DMT stoppers and 854 stayers was similar (adjusted HR, aHR=1.07, 95% CI 0.84 to 1.37; p=0.584), while time to confirmed disability progression was significantly shorter among DMT stoppers than stayers (aHR=1.47, 95% CI 1.18 to 1.84, p=0.001). The difference in hazards of progression was due mainly to patients who had not experienced disability progression in the prebaseline treatment period. Conclusions: Patients with MS who discontinued injectable DMT after a long period of relapse freedom had a similar relapse rate as propensity score-matched patients who continued on DMT, but higher hazard for disability progression.